A STUDY ON SOCIO-ECONOMIC AND CULTURAL STATUS OF GUJJARS AND BAKARWALS IN KASHMIR - Ahmad Mir, Dr. Bilal (Universitas Efarina, 2021)
In 1991 the Gujjar-Bakarwals were granted tribal status in Jammu and Kashmir by the Indian government after conducting a study. The study revealed that Bakarwal is another name of Gujjars entered in revenue records which is why both the names (Gujjars and Bakarwals) were included while the community was enlisted in tribal category in Indian constitutions. Bakarwals belong to the same ethnic stock as the Gujjars, and inter-marriages freely take place among them. The Gujjars of Kashmir reside in far-flung areas and are suffering from various socio-economic problems like as, having no road links, child labour, low percentage of literacy among Gujjar woman, unemployment in educated Gujjar youths, less opportunities of coaching for admission in professional and technical institutions, poor economic conditions etc. So, the present study will focus on current socio-economic and cultural status among Gujjar’S and Bakarwals in Kashmir. Based on findings of the study, the multiple suggestions and recommendations will be helpful for policy makers for framing several policies in order to uplift of their condition.